2018
DOI: 10.1049/htl.2018.5079
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Microsoft's HoloLens with vuforia tracking for neuronavigation

Abstract: Major hurdles for Microsoft's HoloLens as a tool in medicine have been accessing tracking data, as well as a relatively high-localisation error of the displayed information; cumulatively resulting in its limited use and minimal quantification. The following work investigates the augmentation of HoloLens with the proprietary image processing SDK Vuforia, allowing integration of data from its front-facing RGB camera to provide more spatially stable holograms for neuronavigational use. Continuous camera tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 22 publications
1
70
0
Order By: Relevance
“…The accuracy of the Vuforia SDK integration with the Microsoft HoloLens has been previously studied for a neuronavigational app, and is reported to have a mean hologram drift of 1.41 mm. 10 While accuracy was outside the scope of this current study, these results could be veri ed through methods described by Frantz et al in a future study. 10 Future accuracy measures could verify patient safety and pre-procedural plan con dence for INRs.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The accuracy of the Vuforia SDK integration with the Microsoft HoloLens has been previously studied for a neuronavigational app, and is reported to have a mean hologram drift of 1.41 mm. 10 While accuracy was outside the scope of this current study, these results could be veri ed through methods described by Frantz et al in a future study. 10 Future accuracy measures could verify patient safety and pre-procedural plan con dence for INRs.…”
Section: Discussionmentioning
confidence: 65%
“…10 While accuracy was outside the scope of this current study, these results could be veri ed through methods described by Frantz et al in a future study. 10 Future accuracy measures could verify patient safety and pre-procedural plan con dence for INRs.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Automated registration of the 3D model to CT grid was performed using computer vision and Vuforia 9.0.12 with the CT grid as the image target. Features on the CT grid can be reliably and quickly detected by Vuforia 12 , and studies have validated the accuracy of Vuforia on HoloLens (v1) 10 , 13 17 . Registration accuracies were not directly validated in this study; registration fidelity was confirmed visually by the operator based on complete alignment of the virtual gridlines with the physical gridlines.…”
Section: Methodsmentioning
confidence: 95%
“…Thus, a great variety of two dimensional markers exist, such as AprilTags [1], Aruco [2], and the commercially distributed product Vuforia [3]. Frantz et al use Vuforia markers to realize tracking of a patient with the HoloLens [4] in neurosurgical interventions. Other approaches realize patient tracking through surface or contour matching.…”
Section: Introductionmentioning
confidence: 99%